Population dynamics of Capitella aff. teleta (Polychaeta, Capitellidae) in Gamo Lagoon, northeastern Japan, during a series of restoration works following the 2011 Great East Japan Earthquake and tsunami - Hashimoto, Akane; Sato-Okoshi, Waka (Frontiers in Marine Science, 2022)
Population dynamics of capitellid polychaete Capitella aff. teleta was studied in Gamo Lagoon located in northeast Japan for the subsequent two years from 2016 when a series of restoration work was conducted following the 2011 Great East Japan Earthquake and tsunamis. Capitella aff. teleta was distributed widely from the estuary side where the levee was located to the innermost part, but was more abundant in the innermost part where it was enriched in organic matters. In the lagoon, the daily maximum water level dropped from 2017 to 2018 during the reconstruction of a flow-conducting levee, which blocked water flow and isolated the inner part of the lagoon. Although the density decreased drastically for approximately 11 months under diurnal hypoxia and strong reduction condition, small-sized new recruits were observed and the population recovered quickly after the daily maximum water level increased. In Gamo Lagoon, both C. aff. teleta inhabiting the innermost part and the estuary side of the lagoon contributed to maintain the population by dispersing the planktonic larvae to each other. It was inferred that the maximum water level has a significant effect on the maintenance of C. aff. teleta population in the lagoon, and that the sufficient high water level enables the dispersion of the planktonic larvae to quick recovering the population, suggesting that it is important to keep the water area connected without dividing it.